17+4(3p-2)+3p=

Simple and best practice solution for 17+4(3p-2)+3p= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17+4(3p-2)+3p= equation:


Simplifying
17 + 4(3p + -2) + 3p = 0

Reorder the terms:
17 + 4(-2 + 3p) + 3p = 0
17 + (-2 * 4 + 3p * 4) + 3p = 0
17 + (-8 + 12p) + 3p = 0

Combine like terms: 17 + -8 = 9
9 + 12p + 3p = 0

Combine like terms: 12p + 3p = 15p
9 + 15p = 0

Solving
9 + 15p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 15p = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 15p = 0 + -9
15p = 0 + -9

Combine like terms: 0 + -9 = -9
15p = -9

Divide each side by '15'.
p = -0.6

Simplifying
p = -0.6

See similar equations:

| sinX=-0.79 | | 95.75+95.56+98= | | 3x^2=-9x-54 | | 5/6x-4--2 | | K-17=-17 | | 6y+18-5y=15 | | 3(v-6)-5v=-36 | | 3w(w-6)-3=-3(-5w+5)-2w | | 6x-2=x+13The | | 3[-2(4x+5)+4(5x-5)]= | | 63-4/9 | | -45+5x=6x+32 | | -95.31=x/3 | | 4/7*14/8(y-2) | | 11x-19=23 | | 4log(x)-6=2log(x) | | 23=5(x+3) | | 4lg(x)-6=2lg(x) | | gx=144 | | (x+1)(x-2)=(x-1)(x-1) | | -5/6=3/4n | | (3x-1)/(x-4)=0 | | 5x-8=3x-11+8 | | 2z-12-1=z-25+z | | 3/1728 | | 6(-2-3x)+8= | | -x-4=3x+6 | | -3-3x/21 | | 2(3m-9)-3(m-2)= | | 4x+5=8x+5 | | 7x-2=9x-4 | | 9x-9=19x-19 |

Equations solver categories